The impact of helminths on the response to immunization and on the incidence of infection and disease in childhood in Uganda: design of a randomized, double-blind, placebo-controlled, factorial trial of deworming interventions delivered in pregnancy and early childhood [ISRCTN32849447] - Elliotta, Alison M.; Kizza, Moses; Quigley, Maria A.; Ndibazza, Juliet; Nampijja, Margaret; Muhangi, Lawrence; Morison, Linda; Namujju, Proscovia B.; Muwanga, Moses; Kabatereine, Narcis; Whitworth, James A. G. (Clinical trials, 2007)
Helminths have profound effects on the immune response, allowing long-term survival of parasites with minimal damage to the host. Some of these effects “spill-over”, altering responses to non-helminth antigens or allergens. It is suggested that this may lead to impaired responses to immunizations and infections, while conferring benefits against inflammatory responses in allergic and autoimmune disease. These effects might develop in utero, through exposure to maternal helminth infections, or through direct exposure in later life. Purpose To determine the effects of helminths and their treatment in pregnancy and in young children on immunological and disease outcomes in childhood.
Keywords: Helminths; Immunization; Infection; Disease; Childhood; Deworming; Pregnancy